Politically connected independent board and firm performance - Onong Junus; Mohammad Nasih; Muslich Anshori; Iman Harymawan (Cogent Economics & Finance, 2022)
This research examines the relationship between politically connected independent commissioners and independent directors on firm performance. The sample are all listed companies on the Indonesia Stock Exchange (IDX) from 2010-2017. In this study, we employ the ordinary least squares (OLS) regression model and Heckman's 2SLS test to handle the problem of endogeneity. We document that politically connected independent commissioners did not affect the firm performance. On the contrary, politically connected independent commissioners had a negative relationship to firm performance; this was due to the appointment of independent commissioners and independent directors not based on expertise and knowledge in the financial and managerial company field, based solely on previous work experience. Moreover, our result is robust to the Heckman 2SLS test. Therefore, the result is expected to give insight for public firms and policy regulators, to avoid misunderstandings in decision-making at company owners and management levels.
Keywords: M40; M41; M48; 330; Political connections; firm performance; independent board; independent commissioners; independent directors